Modeling the Red-shanked Douc (Pygathrix nemaeus) distribution in Vietnam using Maxent - Nguyen, Tuan Anh (H. : ĐHQGHN, 2019)
The Red-shanked Douc (Pygathrix nemaeus) is the only douc species recorded in all three countries of Indochina. It is classified as Endangered by IUCN, and is believed to have experienced a major drop of more than 50% of its population over the last 40 years. The known distribution of main P. nemaeus populations in Vietnam ranges from Pu Mat National Park, Nghe An Province in the North to the Kon Ha Nung, Gia Lai Province in the South. In this study, we used Maxent, a species distribution modeling approach that is shown to a have high predictive power even with low number of occurrence records, to predict the current distribution of the Red-shanked Douc in Vietnam based on published records. The results show that P. nemaeus inhabits a region from Nghe An to Kon Tum Province, with areas from Ha Tinh, Quang Binh, Quang Tri, Thua Thien – Hue, Da Nang – Quang Nam Provinces exhibiting the highest potential. With all model parameters already listed here, studies in the future may incorporate more occurrence records to develop better models, or other environmental variables to assess the influence of different factors on the species distribution. The results also suggest that species distribution modeling, coupled with a carefully checked and filtered occurrence dataset, as well as species-specific model fine-tuning and evaluating, can help address many conservation issues in Vietnam